Exploring differences in performance management across public and private providers in primary care : Evidence from Finland and Sweden - Glenngård, Anna Häger ; 0000-0001-7500-4610; Malmi, Teemu (Health Policy, 2025)
We employ a qualitative approach to explore whether and how the use of performance measurement systems differs between public and private providers in Swedish and Finnish primary care, from the perspective of primary care centre managers. The two settings are similar in terms of decentralised healthcare systems but differ in terms of organisation of primary care and governance principles for public and private providers. Our findings highlight the importance of considering contextual factors when interpreting results on differences between public and private providers. We observe a) increased goal clarity and an increased use of management controls when payment is separated from provision, b) a similar use of control practices between public and private providers when they operate under the same governance principles, and c) differences in control practices when the “rules of the game” differ. We identify two actions that can facilitate performance management at the provider level. One is for purchasers or owners to clearly communicate the scope of services for which providers are responsible for to improve their goal clarity. The other is for an actor at the national level to facilitate access to reliable data to enhance appropriate performance management and the sharing of experiences among providers.
Keywords: Contextual factors; Governance principles; Performance management; Performance measurement systems; Primary care; Public and private providers